Iowa Birdline update, September 13, 1988 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1988)
Notes for the Iowa Birdline update for September 13, 1988. Highlights of the update include sightings of a Swainson's Hawk, two Sandhill Cranes, four Ospreys, and numerous Caspian Terns. Also of note were observations of many species of shorebirds, ten species of Warblers, and a discovery of an injured immature Red-shouldered Hawk. Epson - sheet feed